2020
DOI: 10.1177/1049732320938343
|View full text |Cite
|
Sign up to set email alerts
|

Dignity as an Intersubjective Phenomenon: Experiences of Dyads Living With Serious Illness

Abstract: Research results suggest that illness can undermine patients’ dignity and that dignity can be understood as an experience formed in communion with others. The aim of this study was, therefore, to illuminate the meanings of lived experiences of dignity as an intersubjective phenomenon from the perspective of dyads in palliative care. The authors analyzed transcripts from interviews with nine dyads using a phenomenological–hermeneutical method. Within the contexts of the dyadic relationship and the dyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The results also revealed that acknowledging the women's autonomy and personal preferences maintained their level of independence. These findings support recent studies highlighting the importance for older home-dwelling people to uphold the ability to make choices in line with one's value (Persson et al, 2020;Segev et al, 2017). Previous research from Norway and Scotland has revealed that healthcare services do not meet the demands of care of older home-dwelling cancer patients, implying a risk of hindering older people's access to proper end-of-life care (Fjose et al, 2018;Miller & Nevadunsky, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…The results also revealed that acknowledging the women's autonomy and personal preferences maintained their level of independence. These findings support recent studies highlighting the importance for older home-dwelling people to uphold the ability to make choices in line with one's value (Persson et al, 2020;Segev et al, 2017). Previous research from Norway and Scotland has revealed that healthcare services do not meet the demands of care of older home-dwelling cancer patients, implying a risk of hindering older people's access to proper end-of-life care (Fjose et al, 2018;Miller & Nevadunsky, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…While usually associated with psychotherapy, in this study-under the influence of the realistic and imagined threats related to cancer-careful listening and intensive responding provides similar therapeutic tools for the participants enabling them, during the interview series, to be able to widely reach and utilize the narrative resources of both personal and social stock of stories (McAdams, 2013;Hänninen, 2004). In contrast to card sets used in some experiential techniques (Stein, 2007), the Clips directly refer to the participants' own life experiences in their own words, being a confirmation of being heard (Martin, 1998) and strengthening participants' dignity (Persson et al, 2020). Besides building on exact citations of the interviewees' speech, the Clip Approach emphasizes the authority of the interviewees (Martin, 1998) through the possibility of them being able to select quotations, to add and remove content, to re-edit the story, and to continue it (Sparkes & Smith, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Seeing severe illness as a family matter, a dyadic concern (Persson et al, 2020), an option to participate as a couple was provided. Ten newly diagnosed prostate cancer patients were recruited to participate in narrative in-depth interviews, five of them individually, and five with their spouse.…”
Section: Methodsmentioning
confidence: 99%
“…In such interactions, intersubjective or social dignity is created. This kind of dignity is explored in a study of dyads living with serious illness ( 9 ). They found that how to respond and being responded to, as well as maintaining emotional bonds and valued activities in daily living within the dyad, are important features to maintain intersubjective dignity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the integrated findings of family members’ perspectives showed that they regard symptom relief, autonomy, independence, respect, being human, self‐image and role preservation as important aspects of dignity for dying patients. A study of the lived experience of intersubjective dignity from a dyadic perspective from dyads living with serious illness in a palliative context showed that being available and upholding continuity were central themes ( 9 ). Today, it is increasingly common that family members have an extensive caring responsibility ( 10 ) and may act as both caregivers and care recipients ( 11 ).…”
Section: Introductionmentioning
confidence: 99%